1998
DOI: 10.1097/00003446-199802000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Spoken Words: The Neighborhood Activation Model

Abstract: Objective-A fundamental problem in the study of human spoken word recognition concerns the structural relations among the sound patterns of words in memory and the effects these relations have on spoken word recognition. In the present investigation, computational and experimental methods were employed to address a number of fundamental issues related to the representation and structural organization of spoken words in the mental lexicon and to lay the groundwork for a model of spoken word recognition.Design-U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

120
1,976
22
22

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,565 publications
(2,140 citation statements)
references
References 78 publications
120
1,976
22
22
Order By: Relevance
“…We compared three different implementations of frequency: frequency operating on resting-activation levels, frequency operating on connection weights, and frequency applied in a postactivation decision rule, as suggested by Luce and colleagues in the NAM (Goldinger et al, 1989;Luce, 1986;Luce & Pisoni, 1998). In each of these simulations, frequency is viewed as a central component of lexical access; that is, frequency plays a role as soon as lexical candidates become active (this is described in more detail below).…”
Section: Simulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…We compared three different implementations of frequency: frequency operating on resting-activation levels, frequency operating on connection weights, and frequency applied in a postactivation decision rule, as suggested by Luce and colleagues in the NAM (Goldinger et al, 1989;Luce, 1986;Luce & Pisoni, 1998). In each of these simulations, frequency is viewed as a central component of lexical access; that is, frequency plays a role as soon as lexical candidates become active (this is described in more detail below).…”
Section: Simulationsmentioning
confidence: 99%
“…(5) would be a frequency-weighted variant of the R. D. Luce (1959) choice rule if TRACE response strengths were used as SWP estimates. While Luce (1986) and Luce and Pisoni (1998) used segmental confusion matrices to estimate SWPs, they also suggested that a TRACE-like interactive activation system could form the front-end to the NAM, such that SWPs would correspond to activations. A key difference in such an implementation compared to the standard TRACE model is the locus of frequency effects.…”
Section: Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is ample evidence in the literature suggesting that phonological overlap among words increases lexical competition (e.g. Allopenna, Magnuson, & Tanenhaus, 1998;Brouwer et al, 2012a;Luce & Pisoni, 1998;McQueen & Viebahn, 2007). We would therefore expect that a casual speaking style should increase lexical competition and slow down word recognition.…”
Section: Introductionmentioning
confidence: 99%